2007
DOI: 10.1097/01.prs.0000264401.19469.ad
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method for Harvest and Processing Fat Grafts: An In Vitro Study of Cell Viability and Survival

Abstract: Fat viability was better when fat was harvested by fine-needle aspiration. The plasticity of mature adipocytes and preadipocytes in vitro suggested that both might be involved in fat graft integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 32 publications
(44 reference statements)
1
44
0
1
Order By: Relevance
“…At this writing, Coleman's technique has been increasingly applied worldwide although often altered by personal modifications. In recent years, many authors have compared the products of different processing methods including sedimentation by gravity [28], washing [28], centrifugation [29][30][31][32][33], and filtering techniques [34][35][36], but their experimental studies have evaluated only single parameters (i.e., cell viability or cell enrichment), leading to biased appraisal of this crucial issue. Thus, the results still are controversial, and surgeons do not currently agree on which method is best for processing fat grafts before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…At this writing, Coleman's technique has been increasingly applied worldwide although often altered by personal modifications. In recent years, many authors have compared the products of different processing methods including sedimentation by gravity [28], washing [28], centrifugation [29][30][31][32][33], and filtering techniques [34][35][36], but their experimental studies have evaluated only single parameters (i.e., cell viability or cell enrichment), leading to biased appraisal of this crucial issue. Thus, the results still are controversial, and surgeons do not currently agree on which method is best for processing fat grafts before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the analysis of fat grafts has been a challenge, many authors are currently developing multiple strategies for determine fat graft performance [12][13][14][15]. To this end our goal was to develop a rapid early method for evaluation of fat grafts that would correlate to late graft performance.…”
Section: Introductionmentioning
confidence: 99%
“…The Coleman technique is considered the gold standard for autologous fat transfer, focusing on gentle syringe aspiration, centrifugation, and minimal volume/multilayer injection technique. However, to date, results of studies comparing cell viability between syringe aspiration and vacuum-assisted liposuction techniques remain conflicting [7][8][9][10].…”
Section: Discussionmentioning
confidence: 98%
“…The current gold standard for fat harvest is the Coleman technique [6], and several studies have reported that the yield of viable adipocytes was higher using this technique compared with vacuum-assisted liposuction [7,8]. Contrary to these findings, some studies have reported favorable results using the vacuum-assisted technique [2,4].…”
Section: Introductionmentioning
confidence: 93%